Active Packaging Based on a PET/PP Food-Grade Film Coated with Pullulan and Clove Essential Oil: Physicochemical and Antimicrobial Properties - Karolina Kraśniewska; Małgorzata Gniewosz (Molecules)
The objective of this study was to design an active packaging material based on a polyethylene terephthalate (PET)/polypropylene (PP) film modified with a pullulan coating enriched with 1, 5, and 10% of clove essential oil (CEO). The physical properties of modified PET/PP films, including opacity, UV, and light visible barrier properties, were evaluated, and calorimetric measurement of color (L*a*b*) was performed, followed by determination of their potential of antioxidant activity and antimicrobial properties against foodborne pathogenic bacteria (E. coli, S. Enteritidis, S. aureus and L. monocytogenes) were characterized. Additionally, the effectiveness of the active packaging in reducing pathogenic bacteria on spinach leaves was evaluated. The PET/PP film with a pullulan coating enriched with CEO did not affect their transparency. The incorporation of CEO improved the film’s UV and visible light barrier properties without causing noticeable color changes while also exhibiting good antioxidant and antimicrobial activity. Furthermore, the application of active packaging effectively inhibited the growth of pathogenic bacteria on spinach leaves, demonstrating its potential for food preservation.